2019
DOI: 10.1021/acsami.9b03830
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Energy and Power Density through Controlling the Concentration of Oxygen Vacancies in V2O5/PEDOT Nanocable-Based Supercapacitors

Abstract: Oxygen vacancies (Vö) play a crucial role in energy storage materials. Oxygen-vacancy-enriched vanadium pentoxide/poly­(3,4-ethylenedioxythiophene) (Vö-V2O5/PEDOT) nanocables were prepared through the one-pot oxidative polymerization of PEDOT. PEDOT is used to create tunable concentrations of Vö in the surface layer of V2O5, which has been confirmed by X-ray absorption near edge structure (XANES) analysis and X-ray photoelectron spectroscopy (XPS) measurements. Applied as electrode materials for supercapaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 61 publications
1
37
0
Order By: Relevance
“…The concentration of each oxidation state of vanadium cations was estimated from the corresponding peak area percentage. The overall vanadium oxidation states of the samples were examined by X‐ray absorption near‐edge structure measurements in the vanadium K‐edge using laboratory‐based instrumentation (University of Washington), and analyzed with a reported methodology . Fitting was performed in Mathematica with the energy from 5460 to 5490 eV, using the function NonlinearModelFit through a linear combination of the spectra of reference compounds.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of each oxidation state of vanadium cations was estimated from the corresponding peak area percentage. The overall vanadium oxidation states of the samples were examined by X‐ray absorption near‐edge structure measurements in the vanadium K‐edge using laboratory‐based instrumentation (University of Washington), and analyzed with a reported methodology . Fitting was performed in Mathematica with the energy from 5460 to 5490 eV, using the function NonlinearModelFit through a linear combination of the spectra of reference compounds.…”
Section: Methodsmentioning
confidence: 99%
“…Beyond the atmospheric treatment and doping, surface coatings such as conductive polymers can also introduce gradient oxygen vacancies in V 2 O 5 through in-situ polymerization. [185][186][187][188] The concentration of oxygen vacancies gradually decrease from the highest concentration at the surface, i.e., the interface between V 2 O 5 and poly (3, 4-ethylenedioxythiophene) (PEDOT), to near zero inside. [186] During cycling, a local electric field develops, which is derived from lopsided charge distribution around oxygen vacancies.…”
Section: Interface Defects and Surface Energymentioning
confidence: 99%
“…[186] DFT calculations showed that migration of oxygen vacancies from the surface of V 2 O 5 inward was thermodynamically favorable, as the Gibbs free energy of formation for vacancies was lower for the inner layers (-306.88 eV) of V 2 O 5 than outer layers (-306.58 eV). [187] Surface defects introduced by atmospheric treatment and polymeric reduction are effective approaches to modify the surface chemistry of electrode materials. The increased surface energy and enhanced electrical conductivity promote the redox kinetics for energy storage.…”
Section: Interface Defects and Surface Energymentioning
confidence: 99%
See 1 more Smart Citation
“…[ 27,28 ] The latter capacity fading commonly stems from a combination of structural changes [ 29 ] and dissolution of vanadium in the electrolyte, especially, in aqueous electrolytes. [ 30 ] Many authors have, therefore, proposed possible solutions to the conductivity problem based on composite electrodes containing conducting polymers [ 31 ] or carbon additives, such as graphene, [ 32 ] carbon nanotubes (CNTs), [ 33 ] or carbon dots. [ 34 ] Likewise, some other nanostructured vanadium oxide and hydroxide materials were also encapsulated in carbonaceous network and showed good electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%